Katekis dan Pastoral Kehadiran: Menjawab Tantangan Zaman melalui Pembinaan Nilai-Nilai Keutamaan Kristiani - Marianus Rago Kristeno; Angelina Febrianty Mukin; Karolina Suwul; Teresia Noiman Derung (Jurnal Penelitian Pendidikan Agama Katolik, 2025)
The role of catechists in the Catholic Church is very important in helping people understand and live Christian teachings through pastoral presence, namely a real presence that builds faith, hope, and love among the people. Catechists are not only teachers, but also spiritual companions who support the daily lives of the people. This study aims to explore the role of catechists in building Christian virtue values ​​while identifying the challenges and opportunities they face in implementing pastoral presence. Through a descriptive qualitative method with a literature study approach, the researcher attempted to analyze literature sources such as books, scientific articles, Church documents and related academic literature. The results of the study show that catechists play an important role in strengthening the faith of the people through teaching, spiritual accompaniment, and strengthening sacramental life, as well as being bearers of hope amidst the various challenges of people's lives. In addition, through pastoral presence, they motivate people to realize love in real actions, such as social service and community solidarity. However, this study also revealed a number of challenges, such as limited training, a shortage of catechists in remote areas, and the influence of modernity that encourages secularization and individualism. The findings show the need for innovation in the pastoral approach, by being present among the people to answer the increasingly diverse needs of the people. This study concludes that the pastoral presence of catechists is a real manifestation of the Church's shepherding and the embodiment of Christ's love among the people. These findings are expected to provide insight into the development of catechist formation programs and more effective pastoral service strategies so that the Church remains relevant in facing changing times and modern challenges, while strengthening the values ​​of Christian virtue among Catholics.